Optimizing Student Engagement in Primary Science and Social Learning: The Feasibility of Contextual Interactive Video Media - Cok Istri Dian Natharani; Anak Agung Gede Agung; Didith Pramunditya Ambara (Universitas Pendidikan Ganesha, 2024)
The lack of interactive, creative, and innovative instructional media provided by educators has resulted in students’ diminished interest and difficulty in concentrating during lessons, thereby leading to lower academic performance. This study aims to develop interactive video media based on the contextual teaching and learning approach for the topic of plant body parts in the fourth-grade science and social curriculum (IPAS) at elementary school. The research employed the ADDIE model, with data collected through observation, interviews, expert evaluations, and trial testing. Data were analyzed using quantitative descriptive analysis techniques. The results of the development of interactive video media indicate that: the design expert judgment test yielded a score of 92.05% in the